Fenomena Independent Woman di Indonesia dan Dampaknya pada Menurunnya Angka Pernikahan 2025 (Kajian Tematik Hadis tentang Larangan Membujang) - Annisatus Sholihah (LPPM IAI Hasanuddin Pare-Kediri, 2025)
The increasing phenomenon of independent women in Indonesia has contributed to the decline in marriage rates and often generates social stigma, even though Islam views the legal status of marriage as flexible. This study raises several issues, namely the influence of independent women on the decreasing number of marriages, the thematic interpretation of the hadith on the prohibition of celibacy, and its relevance to modern social conditions. Using a qualitative-descriptive method with a thematic hadith approach, this research reinterprets the hadith of tabattul and relates it to contemporary social data. The findings indicate that the prohibition of celibacy is not absolute, but rather intended to prevent excessive self-restraint. Thus, the decision of independent women to postpone or not to marry remains in accordance with Islamic law as long as it is based on moral responsibility and the ability to maintain self-discipline.